Effects of intrathecal dexmedetomidine coadministered with hyperbaric bupivacaine in the lower abdominal surgery: Results of a double-blind, randomized, and controlled trial between two different doses - Hazra, Rajdip; Mistry, Manoj; Maitra, Sanjay; Mondal, Koustav (Asian Journal of Medical Sciences, 2023)
Background: Although various adjuvants have been added to local anesthetic agents to potentiate its effect, dexmedetomidine is a relatively new drug with only a fewer studies. Aims and Objectives: The present study has been conducted to compare the efficacy of intrathecal hyperbaric bupivacaine alone with dexmedetomidine of two different doses as adjuvants in spinal anesthesia for the lower abdominal surgery. Materials and Methods: This was a double-blinded, randomized, and controlled trial. Total 120 patients of American Society of Anesthesiologists physical status I and II, 70 male and 50 female, aged between 20 and 60 years, were randomized into three groups receiving 15 mg 0.5% hyperbaric bupivacaine with normal saline, 4 μg (microgram) dexmedetomidine, and 2 μg dexmedetomidine, respectively, administered intrathecally. Results: There was significant difference among all three groups with regard to the onset of sensory block and time to reach the highest level of sensory block. Time to reach T10 dermatome, time to reach Bromage 3 motor block, the mean regression time to S1 dermatome level, the mean regression time to reach Bromage 0, and time to first requirement of rescue analgesia – all these variables showed significance when 4 μg dexmedetomidine additive group was compared with 2 μg dexmedetomidine additive group and bupivacaine alone group. Conclusion: In our double-blinded, randomized, and controlled trial, 4 μg intrathecal dexmedetomidine coadministered with 0.5% hyperbaric bupivacaine showed superior efficacy. Further, larger trials are needed to confirm our findings.